Guaranteeing the independence of the judges of a Multilateral Investment Court: A must for building the Court's credibility - Rishi Gulati; Nikos Lavranos (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
Any future Multilateral Investment Court's independence and impartiality must be guaranteed. If it does not live up to the standards of independence expected of a modern international court, there is little point in contemplating this reform as it is unlikely to remedy the criticisms leveled at the investment arbitration regime.
Keywords: 330